Anke Biendarra. Germans Going Global: Contemporary Literature and Cultural Globalization. Berlin/New York: de Gruyter, 2012. x + 244 pp. - Gabriele Eichmanns Maier (Studies in 20th & 21st Century Literature, 2014)
Review of Anke Biendarra. Germans Going Global: Contemporary Literature and Cultural Globalization. Berlin/New York: de Gruyter, 2012. x + 244 pp.
Keywords: German literature; globalization